O mito de Ngola Ginga Mbandi Kakombe e as suas re-elaborações literárias por Pacavira e Agualusa - Silva, Sílvio Geraldo Ferreira da (2021)
The Queen Ginga Mbandi Kakombe is one of the most celebrated personalities in Angola. In the 17th century, Ginga led a government marked by the imposition of Portuguese rule and, at the same time, negotiations with the aforementioned Europeans. She was an important figure, as her geographical displacements and the struggle to maintain her kingdoms - Ndongo and Matamba - were fundamental elements for the territorial construction of Angola. As a character of importance in the 17th century Angolan socio-political context, she was immortalized as a national myth. Ginga Mbandi can be understood as a woman, at the very least, contradictory. History and literature sought to recreate her figure from different perspectives over time, demonstrating how enigmatic she was. The corpus of this investigation includes the books Nzinga Mbandi (1975), by Manuel Pedro Pacavira, and A Rainha Ginga: e de como os africanos inventaram o mundo (2015), by José Eduardo Agualusa. The justification for this research is the need to know and analyze the woman-myth that Ginga Mbandi Kakombe is considered today. The aim of this work is to present the ngola through different perspectives - literary and historical - and corroborate the maintenance of his memory as an important character for the socio-political, cultural and identity consolidation of Angola.